The Impact of Team Building Intervention on Internal Communication in Lia S Associates Branding & Design Organizations - Setyawan, Andy; Dharmayanti, Diah; Foedjiawati, Foedjiawati (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2020)
This study aims to determine the impact of team building interventions on the internal communication of Lia S Associates Branding & Design. Based on the diagnose results, the organization has a lack of internal organizational communication which results in important information not being conveyed properly and makes employee unable to make decision properly. Therefore researchers conducted team building interventions to improve internal communication. Researcher used the action research method, with three stages namely Pre ODI, ODI and Post ODI. To see the changes after the intervention researchers compared the Pre Test & Post Test results, it was found that there were insignificant changes after the intervention, This is due to the lack of organizational commitment to the intervention process so that the intervention has not been able to bring about changes